Characterization of Temperature Shifts in Terahertz Whispering Gallery Modes Utilizing Comb-Locked Spectroscopy - Müller, Sebastian; Vogt, Dominik Walter; Mayzlin, Yuriy; Puppe, Thomas (Optical Sensors, SENSORS 2024 in Proceedings Optica Sensing Congress 2024, AIS, LACSEA, Sensors, QSM - Part of Optica Sensing Congress, 2024)
We present precision measurements of terahertz whispering gallery mode resonances using a novel comb-locked frequency domain spectrometer. Absolute long-term frequency stability and resolution allows to accurately resolve temperature shifts across multiple modes.
CRIS-Team Scopus Importer:2024-10-25